Analysis and Optimization of Hollow Permanent Magnet Motor Performance and Demagnetization in Intelligent Well Electric Control Sliding Sleeve - Zheng, Yan; Zhong, Junyu; Wang, Xiao; Wang, Long; Dun, Zhiqiang; Ma , Chuanqing; Shi, Yaowei (International Journal of Mechanical and Electrical Engineering, 2025)
High temperatures underground can cause demagnetization in the hollow permanent magnet motor of the intelligent well electric control sliding sleeve, affecting the motor's output performance. To address this issue, this paper establishes a finite element simulation model for the motor and, through comparative analysis, selects the outer rotor type hollow permanent magnet motor solution. Environmental temperature and motor structure are the main factors affecting the performance and demagnetization of the intelligent well electric control sliding sleeve permanent magnet motor. Using Taguchi methods and simulation experimental data, the motor structure is optimized. The optimized motor parameter combination is a slot opening width of 2mm, an air gap of 0.3mm, a pole arc coefficient of 0.76, and a permanent magnet thickness of 3.1mm. After optimization, the motor torque increased by 17.219%, the cogging torque decreased by 27.521%, the demagnetization rate decreased by 55.223%, and the efficiency decreased by only 0.149%. After optimization, the torque difference of the motor increased, the motor's working capacity improved, the torque ripple rate also increased, and its stability decreased slightly, but still within an acceptable range.